2018
DOI: 10.1111/jols.12087
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Practicalities, and PACE s. 24: The Subsuming of the Necessity Criteria in Arrest Decision Making by Frontline Police Officers

Abstract: PACE, as amended by the Serious Organised Crime and Police Act 2005, establishes a complex framework of factors that police officers must consider during arrest decision making. Officers must possess a reason to arrest, it must be necessary to arrest for that reason, and they must give at least a ‘cursory consideration’ to alternatives. Based on a four‐year ethnographic study of frontline officers from two forces in Northern England, we argue that the 2005 reforms have not achieved their aims. The new regime t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…As opposed to foot patrols, the majority of studies that looked at traffic stops measure the self-initiated activity itself and not its outcomes. Pearson and associates (2018) found in Milwaukee, WI, that the incidence of self-initiated traffic stops did not differ between treatment and control groups. A follow-up study in Milwaukee by Lawrence and Peterson (2020) also found no difference in the levels of self-initiated traffic stops between the two groups although there were differences based on the race and gender of the officers.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…As opposed to foot patrols, the majority of studies that looked at traffic stops measure the self-initiated activity itself and not its outcomes. Pearson and associates (2018) found in Milwaukee, WI, that the incidence of self-initiated traffic stops did not differ between treatment and control groups. A follow-up study in Milwaukee by Lawrence and Peterson (2020) also found no difference in the levels of self-initiated traffic stops between the two groups although there were differences based on the race and gender of the officers.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…In New Zealand (NZ) and the UK, offenders are often not arrested and taken into custody (e.g., issued with a warning, or charged and summoned to court) so arrests are poorer indicators of cases being 'cleared' or solved, or of recidivism, than in countries such as the US where arrests are more common (compare for example, Baughman, 2020;Pearson et al, 2018). Other jurisdictional variations include the extent to which suspect descriptions and modus operandi are recorded in structured fields that facilitate analysis (Davies & Woodhams, 2019;Fox et al, 2020).…”
Section: Potential Of Police Crime Datamentioning
confidence: 99%
“…To explain this unexpected finding, the authors suggested that police officers may be less assertive when equipped with a BWC, thereby increasing their vulnerability to assault (Ariel et al, 2016). More recent research supports this suggestion, revealing concerns among some police officers that BWCs will lead officers to use less force than is necessary, thereby putting their safety at risk (Newell and Greidanus, 2018; Pearson et al, 2018).…”
Section: Bwcs and Officer Safety: What We Know From The Policing Contextmentioning
confidence: 99%